Neuroimmune Pathophysiology in Asthma - Pavón-Romero, Gandhi F.; Serrano-Pérez, Nancy Haydée; García-Sánchez, Lizbeth; Ramírez-Jiménez, Fernando; Terán, Luis M. (Frontiers in Cell and Developmental Biology, 2021)
Asthma is a chronic inflammation of lower airway disease, characterized by bronchial hyperresponsiveness. Type I hypersensitivity underlies all atopic diseases including allergic asthma. However, the role of neurotransmitters (NT) and neuropeptides (NP) in this disease has been less explored in comparison with inflammatory mechanisms. Indeed, the airway epithelium contains pulmonary neuroendocrine cells filled with neurotransmitters (serotonin and GABA) and neuropeptides (substance P[SP], neurokinin A [NKA], vasoactive intestinal peptide [VIP], Calcitonin-gene related peptide [CGRP], and orphanins-[N/OFQ]), which are released after allergen exposure. Likewise, the autonomic airway fibers produce acetylcholine (ACh) and the neuropeptide Y(NPY). These NT/NP differ in their effects; SP, NKA, and serotonin exert pro-inflammatory effects, whereas VIP, N/OFQ, and GABA show anti-inflammatory activity. However, CGPR and ACh have dual effects. For example, the ACh-M3 axis induces goblet cell metaplasia, extracellular matrix deposition, and bronchoconstriction; the CGRP-RAMP1 axis enhances Th2 and Th9 responses; and the SP-NK1R axis promotes the synthesis of chemokines in eosinophils, mast cells, and neutrophils. In contrast, the ACh-α7nAChR axis in ILC2 diminishes the synthesis of TNF-α, IL-1, and IL-6, attenuating lung inflammation whereas, VIP-VPAC1, N/OFQ-NOP axes cause bronchodilation and anti-inflammatory effects. Some NT/NP as 5-HT and NKA could be used as biomarkers to monitor asthma patients. In fact, the asthma treatment based on inhaled corticosteroids and anticholinergics blocks M3 and TRPV1 receptors. Moreover, the administration of experimental agents such as NK1R/NK2R antagonists and exogenous VIP decrease inflammatory mediators, suggesting that regulating the effects of NT/NP represents a potential novel approach for the treatment of asthma.